A Gibbs energy balance model for the isothermal ferrite-to-austenite transformation. (15th March 2020) - An, Dong; Pan, Shiyan; Ren, Qingqiang; Li, Qian; Krakauer, Bruce W.; Zhu, Mingfang
Abstract: A Gibbs energy balance (GEB) model for the ferrite (α)-to-austenite (γ) transformation is developed based on the mixed-mode concept and applied to study the isothermal α→γ transformation at the intercritical temperature of 760 °C in Fe-C-Mn and Fe-C-Mn-Si alloys. Both transformation kinetics and stable γ-volume fraction are found to decrease due to the Gibbs energy dissipation caused by the Mn diffusion inside the interface. The decreased interface mobility leads to a slower transformation rate, but has a negligible effect on the stable γ-volume fraction. The transformation kinetics predicted by the GEB model compares reasonably well with the dilatometric measurement. Graphical abstract: Image, graphical abstract